Consumable electrode CO2 gas shield flux-cored wire suitable for cryogenic high manganese steel welding

By using a specially made CO2 gas-resistant flux core welding wire, the composition of its flux core and low carbon steel strips is used to solve the problems of high manganese austenitic steel welding materials in continuous welding and efficient welding, achieving high strength, good molding and low pore sensitivity welding effects.

CN119525820APending Publication Date: 2025-02-28TIANJIN SAINTEAGLE WELDING CO LTD

Patent Information

Application Number
CN202411807420.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing high manganese austenitic steel welding materials are difficult to achieve continuous welding and efficient welding, and the pore sensitivity is high in the oxidizing gas atmosphere, which affects the weld forming effect.

Method used

The melting electrode CO2 gas-friendly flux-core welding wire suitable for deep-cold high manganese steel welding, which is composed of flux-core and low-carbon steel strip. The flux-core contains a specific proportion of rutile, electrolytic manganese metal, potassium sodium titanate and other components, and is welded by CO2 gas protection.

Benefits of technology

It has achieved good welding performance of high manganese austenitic steel, including high tensile strength, yield strength and elongation, and has good impact toughness under low temperature conditions. It has simple welding process, less splashing, and good slag removal performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179633470000041
    Figure BDA0005179633470000041
  • Figure BDA0005179633470000051
    Figure BDA0005179633470000051
  • Figure BDA0005179633470000061
    Figure BDA0005179633470000061
Patent Text Reader

Abstract

The invention belongs to the technical field of welding, and particularly relates to a consumable electrode CO2 gas shield flux-cored wire suitable for cryogenic high manganese steel welding, and a flux core accounts for 25-30% of the total weight of the flux-cored wire; the flux core comprises, by weight, 25%-35% of rutile, 30%-34% of electrolytic manganese metal, 1%-5% of potassium sodium titanate, 2%-5% of quartz, 1%-3% of zircon sand, 0-0.5% of manganese ore, 1%-3% of rare earth ferrosilicon alloy, 0.5%-1.5% of rare earth fluoride, 3%-8% of high-carbon ferrochrome, 2%-4% of molybdenum powder, 2%-4% of magnesium-calcium alloy, 3%-7% of aluminum-zirconium alloy, 9%-12% of nickel-magnesium alloy, 0.5%-1.5% of rare earth silicon-calcium alloy and the balance flux. 1-1.5% of bismuth oxide, 0.5-1.5% of graphite and the balance of iron powder. The invention provides the consumable electrode CO2 gas shield flux-cored wire which is good in process and mechanical property, simple in production process and suitable for cryogenic high manganese steel welding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding, and in particular relates to a consumable CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding. Background Art

[0002] The liquefaction temperature of LNG (liquefied natural gas) is -162℃, so it needs to be stored and transported at low temperatures. The current mainstream storage tank material is 9% Ni steel. 9% Ni steel is expensive, and fields such as storage tank manufacturing have begun to try to replace it with high manganese austenitic steel. High manganese austenitic steel has the advantages of high performance (excellent low temperature performance, fatigue resistance and corrosion resistance) and low cost, which fully meets the construction requirements of LNG storage and transportation equipment and has a good application prospect. In order to promote its use, the market needs its supporting welding materials, and the requirements for it are: the content of the main chemical elements matches that of the parent material; full austenitic structure; good mechanical stability, with twinning as the main deformation mechanism; low crack sensitivity.

[0003] At present, the main welding material for high manganese austenitic steel is electric welding rod. Due to the form of welding materials, it is difficult to weld continuously and is not suitable for high heat input and fast welding. The advantage of flux-cored wire is that compared with electric welding rod, it can be fast and continuous welding with high heat input and continuous welding, and compared with submerged arc, it can be welded in all positions, which makes the production efficiency of flux-cored wire higher.

[0004] The flux-cored welding wires disclosed in "A Metal Powder Cored Flux-Cored Welding Wire for Ultra-low Temperature High Manganese Steel Using Metallic Electrode Gas Shielded Welding" (CN109623199A) and "Flux-Cored Welding Wire for Ultra-low Temperature High Manganese Steel Suitable for All-position Welding and Its Application" (CN113547255A) are both metal powder core type. Although they have higher welding efficiency and certain all-position welding performance, their all-position weld forming effect and porosity susceptibility in an oxidizing gas atmosphere are somewhat inferior to those of slag type flux-cored welding wires. In the patented technologies provided in "A flux-cored welding wire for ultra-low temperature high manganese steel using gas shielded arc welding" (CN112894199A) and "A flux-cored welding wire for high manganese austenitic low temperature steel using gas shielded arc welding" (CN116352312A), the chemical compositions of C and Mn in the steel strip are 0.1-0.2wt% and 0.3-0.6wt%, 3-7wt% and 26-28wt%, respectively, which belong to the category of high manganese steel. During the drawing process of the flux-cored welding wire, work hardening is prone to occur, resulting in wire breakage, which brings considerable difficulties to the production of welding wire. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problems existing in the known technology and to provide a consumable electrode CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, which has good process and mechanical properties and a simple production process.

[0006] The technical solution adopted by the present invention to solve the technical problems existing in the known technology is:

[0007] The invention discloses a CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding. The CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding comprises a flux core and a low-carbon steel strip coated on the outside of the flux core.

[0008] The flux core accounts for 25-30% of the total weight of the welding wire;

[0009] The core comprises the following components in weight percentage: 25-35% rutile, 30-34% electrolytic manganese metal, 1-5% potassium sodium titanate, 2-5% quartz, 1-3% zircon sand, 0-0.5% manganese ore, 1-3% rare earth ferrosilicon alloy, 0.5-1.5% rare earth fluoride, 3-8% high carbon ferrochrome, 2-4% molybdenum powder, 2-4% magnesium calcium alloy, 3-7% aluminum zirconium alloy, 9-12% nickel magnesium alloy, 0.5-1.5% rare earth silicon calcium alloy, 1-1.5% bismuth oxide, 0.5-1.5% graphite, and the rest iron powder. The weight percentage ratio of magnesium calcium alloy, aluminum zirconium alloy, and nickel magnesium alloy is about 1: (1-3): (3-5).

[0010] The CO2 gas shielded flux-cored welding wire for deep-cold high manganese steel welding of the present invention can be used for welding high manganese austenitic steel, and has good process and mechanical properties. Its deposited metal tensile strength is ≥660MPa; yield strength is ≥400MPa; elongation is ≥30%; Akv is ≥60J at -196℃.

[0011] The present invention can also adopt the following technical solutions:

[0012] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the rutile are: TiO2≥95%, C≤0.03%, S≤0.02%, P≤0.03%.

[0013] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the electrolytic manganese metal are: Mn≥99.7%, C≤0.03%, S≤0.021%, P≤0.003%.

[0014] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the potassium sodium titanate are: TiO2≥70%, K2O+Na2O≥20%, S≤0.05%, P≤0.005%.

[0015] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the quartz are: SiO2≥95%, Fe2O3≤0.5%, S≤0.04%, P≤0.04%.

[0016] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the zircon sand are: ZrO2≥60%, SiO2≥25.0%, C≤0.1%, S≤0.05%, P≤0.05%.

[0017] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the manganese ore are: MnO≥99%, S≤0.03%, P≤0.01%.

[0018] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentage of each chemical component in the rare earth ferrosilicon alloy is: 20%≤RE≤30%, Si≤44%, Mn≤3%.

[0019] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentage of each chemical component in the rare earth fluoride is: ΣR2O3≥83%, F≥26%.

[0020] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the high-carbon ferrochrome are: Cr: 62-72%, C: 6.0-9.5%, S≤0.020%.

[0021] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the molybdenum powder are: Mo≥99.90%, C≤0.005%, P≤0.010%.

[0022] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the magnesium-calcium alloy are: Mg: 60% to 70%, Ca: 30%-40%.

[0023] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the aluminum-zirconium alloy are: Al: 40%-60%, Zr: 40%-60%.

[0024] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the nickel-magnesium alloy are: Ni: 70% to 85%, Mg 15% to 30%.

[0025] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentages of the chemical components in the rare earth silicon-calcium alloy are: RE: 10-15%, Ca: 10-15%, Si≤60%.

[0026] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentage of each chemical component in the bismuth oxide is: Bi2O3≥99.90%.

[0027] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentage of each chemical component in the graphite is: C ≥ 98.50%, S ≤ 0.050%;

[0028] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the weight percentage of each chemical component in the iron powder is: Fe≥98.0%, Mn≤0.4%, Si≤0.15%, C≤0.05%, S≤0.020%, P≤0.020%.

[0029] In the above-mentioned CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the chemical composition of the low-carbon steel strip is: C: 0.015-0.030wt%, Si≤0.028%, Mn is 0.12~0.25wt%, P≤0.025wt%, S≤0.030wt%, and the remainder is Fe and unavoidable impurities.

[0030] In the above-mentioned CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, further, the diameter of the welding wire is φ1.4mm.

[0031] In summary, the present invention has the following advantages and positive effects:

[0032] 1. The present invention is a consumable electrode CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding. It is suitable for welding under CO2 gas protection and can be used for welding high-manganese austenitic steel. By adding magnesium-calcium alloy, aluminum-zirconium alloy and nickel-magnesium alloy in appropriate proportions and ratios in the formula, excessive oxidation of Mn is prevented, so that the content of main chemical elements can match that of the parent material, the structure is fully austenite, and it has good mechanical properties. The tensile strength of the deposited metal is ≥660MPa; the yield strength is ≥400MPa; the elongation is ≥30%; and Akv is ≥60J at -196°C.

[0033] 2. The CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding of the present invention can be used to weld high-manganese austenitic steel, is easy to operate, has good process performance, less spatter, better slag removal, beautiful weld formation, good all-position weldability and low dust generation, and can be used for welding under carbon dioxide gas protection, with strong anti-porosity ability.

[0034] 3. The CO2 gas-shielded flux-cored welding wire for deep-cold high-manganese steel welding of the present invention adopts a low-carbon steel strip, is not prone to work hardening and wire breakage during the drawing process of the flux-cored welding wire, and has a simple production process.

[0035] 4. The CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding of the present invention purifies the weld and refines the grains by adding appropriate proportions of rare earth ferrosilicon alloy, rare earth fluoride, and rare earth calcium silicon alloy into the formula, thereby ensuring good mechanical stability of the weld structure, twinning as the main deformation mechanism, and low crack sensitivity. DETAILED DESCRIPTION

[0036] Embodiment 1-5:

[0037] A consumable electrode CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, comprising a flux core and a low-carbon steel strip coated on the outside of the flux core, wherein the flux core accounts for 25-30% of the total weight of the welding wire; the flux core comprises the following components in percentage by weight:

[0038]

[0039]

[0040] The weight percentages of the chemical components in the rutile are: TiO2≥95%, C≤0.03%, S≤0.02%, P≤0.03%; the weight percentages of the chemical components in the electrolytic manganese are: Mn≥99.7%, C≤0.03%, S≤0.021%, P≤0.003%; the weight percentages of the chemical components in the potassium sodium titanate are: TiO2≥70%, K2O+Na2O≥20%, S≤0.05%, P≤0.005%; the weight percentages of the chemical components in the quartz are: SiO2≥95%, Fe2O3≤0.5%, S≤0.04%, P≤0.04%; the zirconium The weight percentages of the chemical components in the quartz sand are: ZrO2≥60%, SiO2≥25.0%, C≤0.1%, S≤0.05%, P≤0.05%; the weight percentages of the chemical components in the manganese ore are: MnO≥99%, S≤0.03%, P≤0.01%; the weight percentages of the chemical components in the rare earth ferrosilicon alloy are: 20%≤RE≤30%, Si≤44%, Mn≤3%; the weight percentages of the chemical components in the rare earth fluoride are: ΣR2O3≥83%, F≥26%; the weight percentages of the chemical components in the high carbon ferrochrome are: Cr: 62-72%, C: 6.0-9.5%, S≤0. 020%; the weight percentages of the chemical components in the molybdenum powder are: Mo ≥ 99.90%, C ≤ 0.005%, P ≤ 0.010%; the weight percentages of the chemical components in the magnesium-calcium alloy are: Mg: 60%-70%, Ca: 30%-40%; the weight percentages of the chemical components in the aluminum-zirconium alloy are: Al: 40%-60%, Zr: 40%-60%; the weight percentages of the chemical components in the nickel-magnesium alloy are: Ni: 70%-85%, Mg15%-30%; the weight percentages of the chemical components in the rare earth silicon-calcium alloy are: RE: 10-15%, Ca: 10-15%, Si ≤ 60%; the oxygen The weight percentages of the chemical components in the bismuth oxide are: Bi2O3≥99.90%; the weight percentages of the chemical components in the graphite are: C≥98.50%, S≤0.050%; the weight percentages of the chemical components in the iron powder are: Fe≥98.0%, Mn≤0.4%, Si≤0.15%, C≤0.05%, S≤0.020%, P≤0.020%; the chemical composition of the low-carbon steel strip is: C: 0.015-0.030wt%, Si≤0.028%, Mn is 0.12-0.25wt%, P≤0.025wt%, S≤0.030wt%, and the balance is Fe and unavoidable impurities.

[0041] The diameter of the welding wire is φ1.4 mm.

[0042] test:

[0043] The CO2 gas-shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding prepared in Examples 1-5 was randomly selected, and welding was carried out under the protection of CO2 gas (CO2 gas purity: ≥99.98%), with a welding voltage of 22 to 30 V, a current of 180 to 300 A, a welding speed of 800 to 1500 mm / min, and a gas flow rate of 20 to 25 L / min. The welding process performance (weld formation, arc stability, weld slag removal, welding spatter rate, etc.) of the flux-cored welding wire was evaluated. After testing, the arc stability was good, the weld quality was high, the slag removal performance was good, the spatter was small, and the process performance was good. The evaluation results are shown in Table 1.

[0044] Table 1 Welding performance evaluation table

[0045]

[0046]

[0047] Further, multiple mechanical properties of structural steel welded with the CO2 gas shielded flux-cored welding wire suitable for deep-cold high manganese steel welding of Examples 1-5 were tested. The specific experimental method is as follows: the deposited metal mechanical property test piece is prepared according to GB / T25774.1, wherein the test piece type is 1.3 and the test plate width is not less than 125 mm. The deposited metal tensile test is carried out according to GB / T2652, and the V-notch impact test is carried out according to GB / T2650. The specific experimental data are shown in Table 2.

[0048] Table 2 Properties of deposited metal after welding with welding wires prepared in Examples 1-5

[0049]

[0050] Table 2 Chemical composition of deposited metal after welding with welding wires prepared in Examples 1-5

[0051]

[0052]

[0053] Compared with other embodiments, in Example 1, the arc stability is very good due to the addition of more rutile and potassium sodium titanate;

[0054] In Example 2, compared with other examples, since more silicate minerals such as quartz and zircon sand are added, the silicate minerals in the rutile slag system can adjust the melting point and viscosity of the slag while slag making, so that the slag coverage is very good;

[0055] Compared with other embodiments, Example 3 has very good slag removal performance due to the addition of more bismuth oxide;

[0056] Compared with other embodiments, in Embodiment 4, due to the addition of more magnesium-calcium alloy, aluminum-zirconium alloy and nickel-magnesium alloy, Mn oxidation is well prevented, so that the weld obtains a complete austenite structure, and the low-temperature brittle transition temperature is reduced, thereby improving the weld metal strength and low-temperature impact toughness;

[0057] Compared with other embodiments, Example 5 contains more rare earth ferrosilicon alloy, rare earth fluoride, and rare earth calcium silicon alloy, which are combined with low-melting point substances such as S to reduce the segregation of low-melting point substances during the solidification of the deposited metal, reduce the tendency of thermal cracks, and refine the grains of the weld metal, effectively improving the elongation of the weld metal and maintaining high-toughness performance, making its elongation and toughness very good.

[0058] Among them, the effects of each component in the present invention are as follows:

[0059] Rutile: Within the scope of the present invention, it can play a good role in slag formation, improving slag coverage and slag removal, and stabilizing the arc. The main component TiO2 has a high slag solidification temperature. The role of TiO2 is to adjust the slag solidification speed, so that the slag becomes short slag and improves the adaptability of the welding position. If too much is added, the slag will be sticky, resulting in poor slag fluidity, difficult slag removal and unsightly molding, and at the same time, it will have an adverse effect on the mechanical properties; if too little is added, it cannot play the role of slag formation and arc stabilization, resulting in incomplete slag coverage and affecting the process performance of the welding material. Therefore, the percentage of rutile in the total weight of the flux core powder is preferably 25-35%.

[0060] Electrolytic manganese: To ensure that the Mn content in the chemical composition of the weld is equivalent to that of the parent material, in the present invention, manganese no longer plays the role of a deoxidizer, but mainly acts as an alloying agent to infiltrate a large amount of Mn elements into the weld, so that the weld obtains a complete austenite structure, reduces the low-temperature brittle transition temperature, and thus improves the low-temperature impact toughness of the weld metal; when the manganese content is too low, it is insufficient to form a single austenite structure; when the manganese content is too high, the tensile strength will be reduced. Therefore, the percentage of electrolytic manganese in the total weight of the flux core powder is 30-34%.

[0061] Potassium sodium titanate: stabilizes the arc and improves the spreading. Therefore, the percentage of potassium sodium titanate in the total weight of the core powder is preferably 4-10%.

[0062] Quartz: The main component is SiO2. Its main function is to adjust the fluidity of the liquid slag pool, provide the appropriate viscosity for the slag, and facilitate molding. The right amount of quartz can provide good coverage for the welding slag. Since quartz is an acidic oxide, too much quartz in the powder is not easy to float out, the weld is not spread well, the excess is high, and it is easy to form slag inclusions in the weld, which increases oxygen in the weld and deteriorates the low-temperature toughness. If the amount added is too little, the slag is prone to incomplete coverage. Therefore, it is more appropriate for the percentage of quartz in the total weight of the core powder to be 5-15% in the formula.

[0063] Zircon sand: The main components are ZrO2 and SiO2. First, it has the function of quartz. In addition, ZrO2, as a high melting point oxide, can increase the melting point of welding slag, which can make the welding slag solidify quickly during vertical welding, prevent the molten iron from falling, and obtain a well-formed weld. In addition, the volume changes during the cooling process of the slag, so that the slag shell can be separated from the weld metal smoothly. The high content of zircon sand introduces more acidic oxides into the weld, which is not conducive to low-temperature toughness. Therefore, it is more appropriate for the percentage of zircon sand in the total weight of the core powder to be 5-8% in the formula.

[0064] Manganese ore: The main component is manganese oxide, among which MnO is the highest. MnO is a neutral oxide with a melting point of about 1650℃. The addition of manganese ore has little effect on the slag removal performance of the slag, but it has a great influence on the weld forming performance. When the amount is large, serious indentations and pitting will appear. Therefore, it is more appropriate for the percentage of zircon sand in the total weight of the core powder in the formula to be 0-0.5%.

[0065] Rare earth fluoride, rare earth ferrosilicon alloy, rare earth calcium silicon alloy: Rare earth elements can combine with low melting point substances such as S to reduce the segregation of low melting point substances during the solidification of the deposited metal and reduce the tendency of thermal cracks. In addition, it can refine the grains, thereby improving the impact toughness. However, if the amount is too high, the droplet transition will slow down, thus affecting the welding processability. Therefore, the percentage of 3-7% of the total weight of the flux core powder is appropriate.

[0066] Rare earth ferrosilicon alloy: In addition to the role of rare earth, silicon can precipitate and deoxidize. The appropriate Mn / Si can fix the oxygen element in the weld well, generate oxidized substances that enter the slag and purify the weld metal. Therefore, the percentage of the total weight of the core powder is preferably 2-4%.

[0067] Rare earth fluoride: In addition to the role of rare earth, fluorine can reduce the content of diffusible hydrogen in the deposited metal, purify the weld, reduce the sensitivity of pores, improve the low-temperature impact toughness of the weld, and adjust the crack resistance of the weld. However, if the fluoride content is too high, the arc will be unstable, the spatter will become larger, and the arc sound will become worse during welding. The best effect can be achieved by controlling it within the percentage range of 1-1.5% of the present invention.

[0068] Rare earth silicon calcium alloy: In addition to the effects of rare earth and silicon, adding calcium to the deposited metal can significantly reduce the sulfur content of the weld metal, play a significant role in purifying and modifying the weld metal, and is beneficial to improving the low-temperature impact toughness of the weld. Therefore, the percentage of 0.5-1.5% of the total weight of the flux core powder is more appropriate.

[0069] High carbon ferrochrome: The chromium element in the component can reduce the segregation of Mn at the grain boundary, reduce the tendency of high manganese steel to fracture along the grain, and at the same time improve the ability of high manganese steel to resist high cycle fatigue. However, when the Cr content exceeds a certain amount, coarse chromium compounds will be formed, which will increase the hardenability of the weld and reduce the low-temperature impact toughness of the weld. Since the carbon element will participate in the deoxidation reaction, graphite, as the most simple raw material, will participate in it first. In order to ensure the full austenite structure of the weld, high carbon ferrochrome is selected as a supplement to the carbon element. Therefore, a percentage of 3-8% of the total weight of the core powder is more appropriate.

[0070] Molybdenum powder: Mo can reduce the solid-liquid coexistence zone, thus effectively inhibiting the generation of hot cracks. At the same time, it significantly improves the strength of the weld metal through solid solution strengthening. However, when the content is high, it will promote the formation of martensite by the TRIP (transformation induced plasticity) effect in the weld, reducing the low-temperature toughness of the material. Therefore, a percentage of 2-4% of the total weight of the core powder is more appropriate.

[0071] Magnesium calcium alloy, aluminum zirconium alloy, nickel magnesium alloy: To ensure that the Mn element is not excessively burned and the Mn content of the weld metal is above 20%, the present invention uses a variety of strong deoxidizers for combined deoxidation, including magnesium calcium alloy, aluminum zirconium alloy, and nickel magnesium alloy, and the ratio is about 1: (1-3): (3-5). The alloy obtained by high temperature smelting and other means can promote the uniform distribution of components, thereby improving the deoxidation adequacy. Among them, aluminum and magnesium have a strong affinity for oxygen, and first react with the oxygen decomposed from the high-valent oxide in the early deoxidation; after entering the droplet stage, magnesium has a low boiling point and vaporizes, and aluminum also partially vaporizes under the action of arc heat, covering the droplet and the molten pool, fixing the oxygen from the surrounding oxidizing protective gas; aluminum has a high boiling point and only partially vaporizes, and the remaining aluminum enters the droplet and slag, and precipitation deoxidation reaction occurs inside the droplet and on the slag-droplet interface. The intense reaction at this stage can remove most of the oxygen; some of the unremoved oxygen transitions to the molten pool with the droplet and slag, and aluminum continues to deoxidize in the molten pool until the molten pool solidifies. In order to avoid large-sized inclusions caused by aluminum deoxidation products, the introduction of an appropriate amount of calcium can not only play a deoxidation role, but also modify the aluminum deoxidation products to form a composite product with calcium aluminate as the core, reduce the size of inclusions in the weld, and improve toughness. At the same time, magnesium-calcium alloys can also perform strong desulfurization and dephosphorization to improve the crack resistance of the weld. Zr in aluminum-zirconium alloy has the function of refining grains and improving weld toughness, thus compensating for the solid solution strengthening of the weld. Nickel-magnesium alloy can also transition nickel elements into the weld. Nickel elements can improve the strength and toughness of the weld, but the content cannot be too high. Too high a content will easily lead to excessive weld strength and decreased impact toughness. When too much composite deoxidizer is added, the deoxidation products of magnesium and aluminum increase, which increases the melting point of the slag and accelerates the solidification rate, which is not conducive to the removal of weld gas and will also cause the vertical welding to deteriorate. Therefore, its content should be controlled. Therefore, the percentage of magnesium-calcium alloy, aluminum-zirconium alloy, and nickel-magnesium alloy in the total weight of the flux core powder is more suitable at 14-23%, including 2-4% for magnesium-calcium alloy, 3-7% for aluminum-zirconium alloy, and 9-12% for nickel-magnesium alloy.

[0072] Bismuth oxide: As a surfactant, it improves slag removal, but too much will form low melting point inclusions and deteriorate weld quality. The appropriate amount to be added is 1-1.5%.

[0073] Graphite: Carbon content>95wt%, as an austenite forming element, it works together with Mn to ensure the full austenite structure of the weld. However, when the carbon content in the weld is too low, the weld yield strength is insufficient; and when the carbon content is too high, coarse carbides will be produced in the weld, affecting toughness. Therefore, a percentage of 0.5-1.5% of the total weight of the core powder is more appropriate.

[0074] Iron powder: Adding iron powder to the flux core can improve welding deposition efficiency, stabilize the arc, and reduce spatter. In order to ensure high deposition efficiency, it mainly comes from reduced iron powder or atomized iron powder. The main function is to adjust the powder loose filling ratio to maintain a suitable powder filling rate. Too much iron powder will produce a lot of smoke and dust.

[0075] In summary, the present invention provides a CO2 gas-shielded flux-cored welding wire capable of welding high manganese austenitic steel and having good process and mechanical properties and suitable for deep-cold high manganese steel welding.

[0076] The above embodiments describe the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding, characterized in that: The consumable electrode CO2 gas shielded flux-cored welding wire suitable for deep-cold high-manganese steel welding comprises a flux core and a low-carbon steel strip coated on the outside of the flux core, wherein the flux core accounts for 25-30% of the total weight of the welding wire; the flux core comprises the following components in weight percentage: 25-35% rutile, 30-34% electrolytic manganese metal, 1-5% potassium sodium titanate, 2-5% quartz, 1-3% zircon sand, 0-0.5% manganese ore, 1-3% rare earth ferrosilicon alloy, 0.5-1.5% rare earth fluoride, 3-8% high carbon ferrochrome, 2-4% molybdenum powder, 2-4% magnesium calcium alloy, 3-7% aluminum zirconium alloy, 9-12% nickel-magnesium alloy, 0.5-1.5% rare earth silicon calcium alloy, 1-1.5% bismuth oxide, 0.5-1.5% graphite, and the balance is iron powder.

2. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentage ratio of the magnesium-calcium alloy, the aluminum-zirconium alloy, and the nickel-magnesium alloy is approximately 1:(1-3):(3-5).

3. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the potassium sodium titanate are: TiO2≥70%, K2O+Na2O≥20%, S≤0.05%, and P≤0.005%.

4. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the rare earth fluoride are: ΣR2O3≥83%, F≥26%.

5. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the magnesium-calcium alloy are: Mg: 60%-70%, Ca: 30%-40%.

6. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the aluminum-zirconium alloy are: Al: 40%-60%, Zr: 40%-60%.

7. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the nickel-magnesium alloy are: Ni: 70% to 85%, Mg: 15% to 30%.

8. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the rare earth silicon calcium alloy are: RE: 10-15%, Ca: 10-15%, Si≤60%.

9. The CO2 gas shielded flux-cored welding wire for deep-cold high-manganese steel welding according to claim 1, characterized in that: The weight percentages of the chemical components in the rutile are: TiO2 ≥ 95%, C ≤ 0.03%, S ≤ 0.02%, P ≤ 0.03%; The weight percentages of the chemical components in the electrolytic manganese metal are: Mn ≥ 99.7%, C ≤ 0.03%, S ≤ 0.021%, P ≤ 0.003%; The weight percentages of the chemical components in the quartz are: SiO2≥95%, Fe2O3≤0.5%, S≤0.04%, P≤0.04%; The weight percentages of the chemical components in the zircon sand are: ZrO2≥60%, SiO2≥25.0%, C≤0.1%, S≤0.05%, P≤0.05%; The weight percentages of the chemical components in the manganese ore are: MnO ≥ 99%, S ≤ 0.03%, P ≤ 0.01%; The weight percentage of each chemical component in the rare earth ferrosilicon alloy is: 20%≤RE≤30%, Si≤44%, Mn≤3%; The weight percentages of the chemical components in the high carbon ferrochrome are: Cr: 62-72%, C: 6.0-9.5%, S≤0.020%; The weight percentages of the chemical components in the molybdenum powder are: Mo ≥ 99.90%, C ≤ 0.005%, P ≤ 0.010%; The weight percentage of each chemical component in the bismuth oxide is: Bi2O3≥99.90%; The weight percentage of each chemical component in the graphite is: C ≥ 98.50%, S ≤ 0.050%; The weight percentage of each chemical component in the iron powder is: Fe ≥ 98.0%, Mn ≤ 0.4%, Si ≤ 0.15%, C ≤ 0.05%, S ≤ 0.020%, P ≤ 0.020%; The chemical composition of the low carbon steel strip is: C: 0.015-0.030wt%, Si≤0.028%, Mn 0.12-0.25wt%, P≤0.025wt%, S≤0.030wt%, and the balance is Fe and unavoidable impurities; The diameter of the flux-cored welding wire is φ1.4 mm.

Citation Information

Patent Citations

  • Gas metal arc welding metal powder core flux-cored wire for ultralow-temperature high-manganese steel

    CN109623199A

  • Gas metal arc welding flux-cored wire used for ultralow-temperature high-manganese steel

    CN112894199A

  • Flux-cored wire suitable for all-position welding and used for ultralow-temperature high manganese steel and application of flux-cored wire

    CN113547255A

  • Gas-shielded flux-cored wire for high-manganese austenite low-temperature steel

    CN116352312A

Cited By

  • High-carbon nitrogen-containing stainless steel flux-cored wire for extremely-low-temperature steel

    CN122462776A